(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Itis high time to understand the process of Social Mobilization done by the NGOsin the above said process and implementing SGSY, it is high time to understandand to documents on what are the various methods followed for socialmobilization while implementing SGSY in their respective areas so that if anyinnovative methods used, it can be popularized and used in the future. Hence the present study would be the miles stone for exploring various methods used and impact made through social mobilization for making the SGSY effective and efficient in the future.